Expression of early transcription factors by mesenchymal stem cells derived from ovine umbilical cord Wharton’s jelly - ESWARI, S; MONISHA, M; VIJAYARANI, K; KUMANAN, K (The Indian Journal of Animal Sciences, 2016)
Mesenchymal stem cells (MSCs) are multipotent stem cells that can differentiate into mesodermal lineages. Despite major progress in our general knowledge related to the application of adult stem cells, finding alternative sources for bone marrow MSCs has remained to be challenged. In this study, we utilized ovine umbilical cord Wharton’s jelly as a primary source for isolation of MSCs since it is a rich source of MSCs and no ethical issues were involved. Ovine umbilical cord Wharton’s jelly segments were digested enzymatically and cultured in vitro in culture medium. In addition to the study of their morphology and colony forming units, the expression of pluripotent stem cell markers by the isolated MSCs were also studied. The MSCs were plastic adherent, clonogenic and their morphology were polygonal, star shaped and fibroblast like. They revealed a strong expression of pluripotent stemness markers Oct4, Sox2, Nanog and Alkaline phosphatase. These cells confirmed their ability of self-renewal by expressing Sox2 gene and their properties of pluripotency and plasticity by expressing Oct4, Nanog and Alkaline phosphatase. The study revealed that Wharton’s jelly is a rich source of stem cells with stemness properties and mesenchymal like morphology and could be used as an alternate for the bone marrow derived MSCs for cell based regenerative therapies.